2020
DOI: 10.1039/d0ra03664a
|View full text |Cite
|
Sign up to set email alerts
|

Combining amino acids and carbohydrates into readily biodegradable, task specific ionic liquids

Abstract: Combining amino acids and carbohydrates yields readily biodegradable ionic liquids with a hydrogen-bond-rich structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 33 publications
0
36
0
Order By: Relevance
“…Chrobok’s group has applied this method to study the glycosylation of d -glucopyranose with halogenoalcohols (e.g., bromoethanol, chloroethanol, 3-chloropropanol, or 3-chloro-1,2-propanediol), generating glycosides with yields of 50% to 78% after purification by column chromatography [ 12 , 15 , 41 , 42 ]. Glycosides can be further quaternized with amines to yield halide salts, which can be applied as task-specific ILs after metathesis with specific anions, such as [NTf 2 ] − [ 12 , 41 ], [MCPA] − , [2,4-D] − [ 15 ], [N(CN) 2 ] − [ 12 ], or amino acid anions [ 42 ]. It has also been reported that triazoles can be obtained via glycosylation of d -xylose with propargyl alcohol, followed by a click reaction and subsequent N -alkylation [ 43 ].…”
Section: Synthesis Of Carbohydrate-derived Ils and Saltsmentioning
confidence: 99%
See 4 more Smart Citations
“…Chrobok’s group has applied this method to study the glycosylation of d -glucopyranose with halogenoalcohols (e.g., bromoethanol, chloroethanol, 3-chloropropanol, or 3-chloro-1,2-propanediol), generating glycosides with yields of 50% to 78% after purification by column chromatography [ 12 , 15 , 41 , 42 ]. Glycosides can be further quaternized with amines to yield halide salts, which can be applied as task-specific ILs after metathesis with specific anions, such as [NTf 2 ] − [ 12 , 41 ], [MCPA] − , [2,4-D] − [ 15 ], [N(CN) 2 ] − [ 12 ], or amino acid anions [ 42 ]. It has also been reported that triazoles can be obtained via glycosylation of d -xylose with propargyl alcohol, followed by a click reaction and subsequent N -alkylation [ 43 ].…”
Section: Synthesis Of Carbohydrate-derived Ils and Saltsmentioning
confidence: 99%
“…Combining carbohydrates with other bio-derived molecules (i.e., amino acids) has also been shown to yield readily biodegradable ILs ( 3a – g ), which can be decomposed in 5–6 days in activated sludge [ 42 ]. This result highlights how carbohydrate-derived ILs can be used as alternatives to the cholinium family of ILs ([Ch]ILs), which have emerged as the most readily biodegradable ILs to date [ 5 ].…”
Section: Properties Of Carbohydrate-based Ilsmentioning
confidence: 99%
See 3 more Smart Citations